The Effect of Supplementary Feeding (PMT) with Broiler Chicken Eggs on the Weight of Stunted Toddlers - Ana Kurnia Putri; Tri Arianingsih; Wasis Pujiati; Cian Ibnu Sina (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Nutritional problems remain a major health concern in Indonesia. According to UNICEF (2024), one in five toddlers experiences stunting, with Natuna Regency showing a prevalence of 18%, higher than the provincial rate of 15.4%. The Serasan Health Center implemented an innovation program called “Pedok Bilis & Bubur Nasi,” requiring stunted toddlers to consume two chicken eggs daily. This study aimed to determine the effect of providing additional food (PMT) using broiler chicken eggs on the body weight of stunted toddlers. The research employed a quasi-experimental one-group pretest–posttest design with 14 toddlers selected through purposive sampling. Weight measurements were taken before and after a 14-day intervention and analyzed using the Wilcoxon test at a 0.05 significance level. Results showed an increase in average body weight from 11.66 kg to 11.97 kg with p = 0.009 (<0.05), indicating a significant effect. Broiler chicken egg supplementation is a simple, effective, and affordable nutritional intervention recommended for primary health care to help reduce stunting rates.